Odpowiedź :
Odpowiedź:
[tex]a)\ \ (-2)^3\cdot(-2)^5=(-2)^{3+5}=(-2)^8=256\\\\\\b)\ \ 3^3\cdot(-3)^3=-3^3\cdot3^3=-3^{3+3}=-3^6=-729\\\\\\c)\ \ \dfrac{2^5\cdot5^5}{10^3}=\dfrac{(2\cdot5)^5}{10^3}=\dfrac{10^5}{10^3}=10^{5-3}=10^2=100\\\\\\d)\ \ [(-1)^{11}]^2:[(-1)^4]^3\cdot(-1)^7=(-1)^2^2:(-1)^1^2\cdot(-1)^7=(-1)^{22-12+7}=\\\\=(-1)^1^7=-1[/tex]
[tex]e)\ \ (1\frac{1}{5})^7\cdot(1\frac{2}{3})^7=(1\frac{1}{5}\cdot1\frac{2}{3})^7=(\frac{\not6^2}{\not5_{1}}\cdot\frac{\not5^1}{\not3_{1}})^7=2^7=128\\\\\\f)\ \ \dfrac{35^4:7^4}{(5^3:5^2)^2}=\dfrac{(35:7)^4}{(5^{3-2})^2}=\dfrac{5^4}{(5^1)^2}=\dfrac{5^4}{5^2}=5^{4-2}=5^2=25\\\\\\g)\ \ (4\cdot4^2)^3:(4^8:4^5)^2=(4^{1+2})^3:(4^{8-5})^2=(4^3)^3:(4^3)^2=4^9:4^6=4^{9-6}=\\\\=4^3=64[/tex]
[tex]h)\ \ [(1\frac{1}{3})^2]^3:(\frac{4}{3})^6=[(\frac{4}{3})^2]^3:(\frac{4}{3})^6=(\frac{4}{3})^6:(\frac{4}{3})^6=1\\\\\\i)\ \ \dfrac{(-12)^8\cdot(-12)^7}{(-12)^1^4}=\dfrac{(-12)^{8+7}}{(-12)^1^4}=\dfrac{(-12)^1^5}{(-12)^{14}}=(-12)^{15-14}=(-12)^1=-12[/tex]